Tryptase potentiates enteric nerve activation by histamine and serotonin: Relevance for the effects of mucosal biopsy supernatants from irritable bowel syndrome patients. Issue 9 (4th April 2017) - Ostertag, D.; Annahazi, A.; Krueger, D.; Michel, K.; Demir, I. E.; Ceyhan, G. O.; Zeller, F.; Schemann, M.
Abstract: Background: We previously showed that mucosal biopsy supernatants from irritable bowel syndrome patients activated neurons despite low concentrations of tryptase, histamine, and serotonin which individually would not cause spike discharge. We studied the potentiating responses between these mediators on excitability of enteric neurons. Methods: Calcium‐imaging was performed using the calcium‐sensitive dye Fluo‐4 AM in human submucous plexus preparations from 45 individuals. Histamine, serotonin, and tryptase were applied alone and in combinations to evaluate nerve activation which was assessed by analyzing increase in intracellular Ca 2+ ([Ca 2+ ]i ), the proportion of responding neurons and the product of both defined as Ca‐neuroindex (NI). Protease activated receptor (PAR) 2 activating peptide, PAR2 antagonist and the serine protease‐inhibitor FUT‐175 were used to particularly investigate the role of proteases. Key Results: Histamine or serotonin (1 μmol/L each) evoked only few small responses (median NI [25%/75%]: 0 [0/148]; 85 [0/705] respectively). Their combined application evoked statistically similar responses (216 [21/651]). Addition of the PAR2 activator tryptase induced a significantly higher Ca‐NI (1401 [867/4075]) compared to individual application of tryptase or to coapplied histamine and serotonin. This synergistic potentiation was neither mimicked by PAR2 activating peptide nor reversed by the PAR2 antagonist GB83, but abolished by FUT‐175. Conclusions & Inferences: We observed synergistic potentiation between histamine, serotonin, and tryptase in enteric neurons, which is mediated by proteolytic activity rather than PAR2 activation. This explained neuronal activation by a cocktail of these mediators despite their low concentrations and despite a relatively small PAR2‐mediated response in human submucous neurons. Abstract : Biopsy supernatants of irritable bowel syndrome patients activate enteric neurons despite the low concentrations of tryptase, histamine, and serotonin which individually would not cause spike discharge. We found that tryptase synergistically potentiated the response to individual and combined application of histamine and serotonin. This potentiation was mediated by proteolytic activity of tryptase rather than protease activated receptor 2 activation. Our findings identified synergism between neuroactive substances as a plausible explanation for their pronounced effects as a cocktail.